Se eu estou com o microfone, eu estou com o poder? Humor produzido por mulheres em performance ao vivo - Sechinato, Juliana Spagnol (2021)
This thesis analyzes the insertion of women as subjects of humor, more specifically of stand-up comedy, whose professional trajectories and performative constructions are marked by difference and the place of inequality they occupy. Based on a qualitative methodology grounded in interviews with 25 research interlocutors, on the analysis of internet videos and bibliographical research, I support the ambivalences in the debates about women as producers of humor, thinking about the key to the exercise of power. I argue that these ambivalences indicate shifts towards those that were not previously considered as producers of humor, while there are permanencies. Through performance studies, studies on laughter and humor, gender studies and studies on women and humor, I seek the comic making of the stand-up comedy and its power effects on the research interlocutors. I analyze the dispute for professional spaces between the circuits of comedians and the performative strategies of the research interlocutors, seeking how these women organize themselves, establishing ties and networks, to produce and create their own scenes and how this movement also reflects a greater diversification of the stand-up consumer audience. I explore the themes of women's narratives in stand-up comedy and argue for how they are motivated by their “annoyances”. Finally, I argued that, with the success of the performance, there is an exercise of power and transit of status by the comedians, who find in stand-up comedy a comedy model that allows them to control the comic narrative of that time and stage space without taking on other characters.